Exercises as a Basis for Foreign-language Encoding-processes - Szczodrowski, Marian (Glottodidactica, 2014)
Various forms of language-activity influence the acquisition of a foreign language. In this article, the author underlines the importance of foreign-language exercises, and their effectiveness in the developing the learner’s encoding of decoded foreign-language information structures in the form of constant structure-matrices. The theories of teaching and learning drawn on in the article point to the variety of methods and degrees of foreign-language acquisition, both through cognitive exercises and through the pattern approach. Such exercises develop receptive and productive language-communication skills.